Implementation of Istiqraiyah Method Through Mind Map in Shorof Learning - Muhammad Al Farobi; Muassomah Muassomah; Muhammad Afiq Aminullah; Titi Mulyanti; Salwa Qozziyatul Mardhiyah; Saardah Aoh-lam (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2023)
This study aimed to describe the steps of applying istiqraiyah method through mind maps in Shorof learning and to find out students' interest in applying istiqraiyah method through mind maps in Shorof learning in Maulana Malik Ibrahim Islamic State University of Malang. This study used mix methods; descriptive qualitative, it describes the steps of applying istiqraiyah method through mind maps in Shorof learning and quantitative, it is to answer students' influence and interest in applying istiqraiyah method through mind maps in Shorof learning. Data collection techniques used interviews, observation, and questionnaires. Quantitative data analysis used the Likert theory to calculate the value of student interest taken from the questionnaire. The results of the study showed that the first step in applying istiqraiyah method through mind maps in Shorof learning is to provide several examples of sentences from al-fi’lul lazim and al-fi’lul muta’adias insights and descriptions, then compiled in a mind map in the form of a definition format, definitions, signs, meanings, wazan, patterns, and ways of changing the usual al-fi’lul lazim to al-fi’lul muta’adi which also begins with various examples. Istiqraiyah method through mind maps in Shorof learning increases the average pre-test and post-test scores of 30.83, which results in a value of 0.73 based on the Gain test, so it is in the high category. As for students' interest in applying istiqraiyah method through mind maps in Shorof learning, it has a presentation index of 73.2% and included in the strong category.